1976
DOI: 10.1136/gut.17.12.925
|View full text |Cite
|
Sign up to set email alerts
|

Effect of motilin on the lower oesophageal sphincter.

Abstract: SUMMARY The effect of motilin on lower oesophageal sphincter (LES) pressure has been studied in unanaesthetised specially trained dogs using an infusion manometric technique. Motilin produced significant rises in resting pressure and contractions of the LES after doses ranging from 0009 ug/kg to 0 05 jug/kg. Doses greater than 005 tg/kg resulted in repetitive high amplitude contractions. Atropine 30 ,ug/kg completely abolished the effect of the lower doses of motilin. Higher doses of motilin in atropinised dog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

1980
1980
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(11 citation statements)
references
References 12 publications
0
10
0
1
Order By: Relevance
“…That increase in LES pressure occurred acutely (within 1–2 min); a similar result was seen in the present study. Other studies have shown that the increase in LES pressure due to motilin receptor agonists is cholinergically mediated [12, 13]. …”
Section: Discussionmentioning
confidence: 99%
“…That increase in LES pressure occurred acutely (within 1–2 min); a similar result was seen in the present study. Other studies have shown that the increase in LES pressure due to motilin receptor agonists is cholinergically mediated [12, 13]. …”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy might be explained by the possibility that NT is not the only regulatory peptide involved in the regulation of LESP. Motilin [6], for instance, may increase LESP; however, this peptide was not evaluated. Furthermore, the vegetative nervous system is also involved in LESP regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Motilin increases the LESP [6], whereas vasoactive intestinal peptide (VIP) reduces the LESP [7]. Gastrin and cholecystokinin were initially thought to be important modulators of LESP but had significant effects only in pharmacological doses [8,9].…”
mentioning
confidence: 99%
“…Motilin bewirkt eine Erhöhung des Sphinkterruhedrucks [16], hingegen hat Neurotensin einen antagonistischen Effekt [17], Stö rungen der Neuroregulation über Mechanorezeptoren im KardiaFundus-Bereich sind auch verantwortlich für das vermehrte Auf treten von transienten Sphinkterrelaxationen im Rahmen der GERD [ 18,14], Auslösend sind dabei wahrscheinlich die erhöhten Druckverhältnisse im Kardiabereich bei Vorliegen einer Hiatus hernie.…”
Section: Introductionunclassified